In Conclusion: A Collection of Summary Talks in High Energy Physics - Bjorken James D (World Scientific, 2004)
This invaluable volume is a collection of conference talks by James D Bjorken, who has made a huge impact on particle physics and the development of the Standard Model. The earliest of these talks was given in 1965, and the latest in 1990. The book provides, from a personal perspective, a glimpse of the complex evolution of the field over those highly productive decades. In Conclusion: A Collection of Summary Talks in High Energy Physics is aimed at a broad spectrum of particle physicists and students, both experimental and theoretical.